Desain Alternatif Struktur Talang Air Beton pada Saluran Sugih, Desa Cibedug, Kecamatan Ciawi - Nopiyansah, Muhammad Ilham; Hariati, Feril; Chayati, Nurul; Insan, Muhammad Khaerul (Universitas Ibn Khaldun, 2023)
ABSTRACT The provision of water in wet farming is very important to support optimal crop yields. The irrigation system on the Sugih Canal in Cibedug Village, Ciawi, Bogor Regency was affected by a landslide with a depth of 8 meters, which resulted in a 28 meter long canal being cut off. This study aims to plan the construction of reinforced concrete gutters with a size of 60 cm and a height of 80 cm to repair broken points. The design of reinforced concrete gutters refers to SNI 03-2847-2002. It is planned that the floor plate thickness is 20 cm and the channel wall thickness is 15 cm, using concrete with quality K-250 (fc' = 25 MPa). Based on the analysis that has been carried out, the live load is 250 kg/m, the dead load is 748 kg/m, and the factored load is 1297.6 kg/m. The maximum moment (Mmax) that occurs at the pin support is 38,281 kNm. Concrete reinforcement on the channel floor plate is in the form of main reinforcement D12-135, and reinforcement for D8-300. Reinforcement for wall plate is main reinforcement D12-115, reinforcement for D8-255.